Kombucha fermentation of African mustard (Brassica tournefortii) leaves: Chemical composition and bioactivity - Rahmani, Rami; Beaufort, Sandra; Villarreal-Soto, Silvia Alejandra; Taillandier, Patricia; Bouajila, Jalloul; Debouba, Mohamed (Food bioscience, 2019)
Brassica tournefortii is an edible vegetable formerly consumed by North African populations. Nowadays, this plant has been neglected and is less used. The present study aims to give an extra nutraceutical value to B. tournefortii using a 2-wk kombucha fermentation process. At the end of incubation, fermented and unfermented (control) B. tournefortii aqueous extracts were successively fractionated with ethyl acetate (EtOAc) and n-butanol to measure their chemical composition and bioactivity. Results showed that kombucha fermentation significantly increased total phenolic content, with the highest amounts in the EtOAc fraction. The antioxidant potential of B. tournefortii leaves was improved by fermentation of EtOAc extracts and conversely lowered in aqueous ones. Anti-acetylcholinesterase activity was increased with fermentation to reach ∼8-fold higher value in B. tournefortii EtOAc and aqueous extracts relative to unfermented samples. Kombucha fermentation was found to reduce cytotoxicity and xanthine oxidase inhibitory effects of B. tournefortii leaves. The findings suggested that fermentation is a promising, simple and safe bioprocess that could improve the food proprieties of less-used edible plants.